Quality assurance standards of e-learning and the basis for their application in preparation of language study plans and the science of holy Qur’an - Ali Hassan, Elsayed Makki Elbishr; Suleiman, Hassan; Li, Ting Lin; Awang, Abdul Bari; Elhag, Ibrahim Babikir; El-Ebiary, Yousef A. Baker (PennWell Publishing Co., 2020)
Ensuring the quality of E-Learning in the field of higher education requires in the first place an institutional vision accompanied by commitment, leadership, and proper planning, while ensuring that this is available to the partners. The E-Learning policy should conform to the overall vision of the institution and the tasks and services they provide. Leaders and managers must be able to explain the reasons for choosing E-Learning as an appropriate learning strategy for the students who serve them. Online education components should include the quality components that were identified in the first part of this post. Additionally, organizations need to comply with the regulations governing online learning and ensure that they are reflected in policies and practices.This research also seeks to establish the rules and foundations of specialized education in the field of teaching Arabic to non-native speakers, and link them to Quran. There is no doubt that all scientific institutions aim to ensure the quality of the application of their academic standards that set them to achieve what they want in the field of raising the level of targeted scientific seekers. Therefore, this paper raises a fundamental research problem, namely, ways to ensure scientific quality. This paper referred to a number of questions, including: What are the standards? What does quality mean in the preparation of language teaching plans and Quranic sciences? And how to find academic content that combines between Arabic and Quranic sciences? What possibilities are there to ensure that learners are improved through quality standards? This paper discusses the concept of educational quality and its role in achieving the objectives of the educational process, addressing the role of scientific standards in the field of the preparation of study plans, indicating the possibilities that must be available to help in thesuccess of the implementation of study plans prepared to teach Arabic and Quranic sciences, taking the descriptive analytical approach. Thus, this paper added a new dimension to the studies that preceded it in this area, where it is to indicate the criteria required to achieve the objectives set by linking the teaching of Arabic language with the science of the Quran. The paper recommends further studies on ensuring that quality standards are applied in the educational process.